2011
DOI: 10.1007/s11252-011-0202-7
|View full text |Cite
|
Sign up to set email alerts
|

Pollinating animals in the urban environment

Abstract: Urban environments contain habitats for flowering plants and their pollinating animal species. It is, however, unclear how the urban matrix influences plant-pollinator processes. We recorded plant diversity, floral abundance, flower visitor diversity and plot visits at 89 plant patches within the city of Zürich. The urban matrix surrounding each site was analyzed for the landscape metrics edge density and the extent of green area up to 200 m radius. The correlation between edge density and bee diversity and vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
89
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(97 citation statements)
references
References 65 publications
7
89
0
1
Order By: Relevance
“…ER/CE are zero models used for generation of random matrices for comparisons with actual results (see Materials and methods), where p stands for the probability that the modelgenerated matrix is equally or more nested than is the actual one. Boldface indicates statistically significant results when both zero models were significantly less nested at p \ 0.05 important insect pollinator groups, e.g., bees (Bates et al 2011;Hennig and Ghazoul 2012;Tonietto et al 2011), hoverflies (Bates et al 2011), sarcophagid flies (Mulieri et al 2011) or butterflies (Dallimer et al 2012;Soga and Koike 2013), all recorded also in our study. Their response, however, may be highly variable and depend on many factors.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…ER/CE are zero models used for generation of random matrices for comparisons with actual results (see Materials and methods), where p stands for the probability that the modelgenerated matrix is equally or more nested than is the actual one. Boldface indicates statistically significant results when both zero models were significantly less nested at p \ 0.05 important insect pollinator groups, e.g., bees (Bates et al 2011;Hennig and Ghazoul 2012;Tonietto et al 2011), hoverflies (Bates et al 2011), sarcophagid flies (Mulieri et al 2011) or butterflies (Dallimer et al 2012;Soga and Koike 2013), all recorded also in our study. Their response, however, may be highly variable and depend on many factors.…”
Section: Discussionmentioning
confidence: 60%
“…Their response, however, may be highly variable and depend on many factors. For instance, the abundance of bee species in urban conditions is positively correlated with floral abundance and diversity (Wojcik 2011), as well as resource distribution (e.g., nesting or egg-laying sites; Hennig and Ghazoul 2012). As shown by the latter authors, diversity and visitation by syrphids in urban conditions can also be related to the presence of a green area.…”
Section: Discussionmentioning
confidence: 99%
“…The availability of pollen and nectar as well as nesting sites within speciesspecific flying distances is important for wild bees to colonize habitats successfully (Westrich 1996;Gathmann and Tscharntke 2002;Zurbuchen et al 2010;Wojcik and McBride 2012). Bees are ectothermic and thermophile organisms, thus the warmer (micro-) climate of cities enables favourable habitat conditions for many wild bee species (Cane 2005;Hennig and Ghazoul 2012). Research on urban sites likely to be populated by wild bees, provides important information for urban planning to enhance wild bee diversity ).…”
Section: Introductionmentioning
confidence: 99%
“…In a review, Hernandez et al (2009) found only 59 research publications worldwide on urban bee ecology and concluded that we are only beginning to document urban bee communities and their dynamics. The interest in urban bee ecology has surged in recent years (Everaars et al 2011;Winfree et al 2011;Hennig and Ghazoul 2012;Banaszak-Cibicka and Zmihorski 2012;Hinners et al 2012;Matteson et al 2013;Verboven et al 2014;Lowenstein et al 2014;Baldock et al 2015). However urbanisation is predicted to increase dramatically, with the number of people living in urban areas reaching 5 billion by 2030 (UN 2011).…”
Section: Introductionmentioning
confidence: 99%